KEMAMPUAN MEMBACA PEMAHAMAN TEKS CERITA RAKYAT BUGIS SISWA KELAS X SMA NEGERI 2 MAROS - Asriani; Syamsudduha, Syamsudduha; Asri, Aswati (Journal Studies in Indonesian Language and Literature, 2024)
This study aims to describe the reading comprehension ability of Bugis folklore texts of class X students of SMA Negeri 2 Maros. This research is descriptive quantitative. The population in this study were all class X students totaling 134 people. The sample set as many as 100 students using simple random sampling technique . The data analysis technique used to collect data in this study is the reading test technique. The data to be collected were analyzed using descriptive analysis techniques. The results showed that the ability to read comprehension of Bugis folklore texts of class X students of SMA Negeri 2 Maros was declared incapable. This can be seen in the percentage of students who scored ≥75 as many as 69 people with a percentage (69%) in the category of not being able to reach the set criteria of 75%.